Social Equity Concerns and Differentiated Environmental Taxes - Jan Abrell; Sebastian Rausch; Giacomo A. Schwarz (ETH Zurich, CER-ETH - Center of Economic Research, 2016)
This paper examines pollution tax differentiation across industries in light of social equity concerns using theoretical and numerical general equilibrium analyses in an optimal tax framework. We characterize the drivers for non-uniform optimal taxes emanating from the interaction of household heterogeneity with social preferences. Quantitatively assessing the case of price-based CO2 emissions control in the U.S. economy, we find that optimal carbon taxes differ largely across industries, even when social inequality aversion is low. Our results are robust with respect to the stringency of the environmental target, non-optimal redistribution schemes, and parametric uncertainty in firms' and households' equilibrium tax responses.
Keywords: H23; Q52; C68; 330; Differentiated environmental taxes; Carbon pricing; Industries; Heterogeneous households; Social inequality; Optimal taxation; General equilibrium; Ökosteuer; Steuergerechtigkeit; Soziale Ungleichheit; Umweltbelastung; Industrie; Privater Haushalt; USA